Associations Between Fathers’ Masculinity Orientation and Anticipated Reaction Toward Their Child’s Coming Out - Kranz, Dirk (Frontiers in Psychology, 2021)
The present study examined associations between fathers’ masculinity orientation and their anticipated reaction toward their child’s coming out as lesbian or gay (LG). Participants were 134 German fathers (28 to 60 years) of a minor child. They were asked how they would personally react if, one day, their child disclosed their LG identity to them. As hypothesized, fathers with a stronger masculinity orientation (i.e., adherence to traditional male gender norms, such as independence, assertiveness, and physical strength) reported that they would be more likely to reject their LG child. This association was serially mediated by two factors: fathers’ general anti-LG attitudes (i.e., level of homophobia) and their emotional distress due to their child’s coming out (e.g., feelings of anger, shame, or sadness). The result pattern was independent of the child’s gender or age. The discussion centers on the problematic role of traditional masculinity when it comes to fathers’ acceptance of their non-heterosexual child.